Vortex Beam Transmission Compensation in Atmospheric Turbulence Using CycleGAN - Tan Qu; Yan Zhang; Jiaji Wu; Zhensen Wu (Photonics, 2023)
To improve the robustness of vortex beam transmission and detection in the face of atmospheric turbulence and to guarantee accurate recognition of orbital angular momentum (OAM), we present an end-to-end dynamic compensation technique for vortex beams using an improved cycle-consistent generative adversarial network (CycleGAN). This approach transforms the problem of vortex beam distortion compensation into one of image translation. The Pix2pix and CycleGAN models were extended with a structural similarity loss function to constrain turbulence distortion compensation in luminance, contrast and structure. Experiments were designed to evaluate the compensation performance from subjective and objective indicators. The simulation results demonstrate that the optical OAM intensity map is very similar to that of the target OAM light after compensation. The mean value of structural similarity is close to 1. The recognition accuracy of the OAM is improved by 4.4% compared to no distortion compensation, demonstrating that the improved CycleGAN-based compensation scheme can guarantee excellent detection accuracy without reconstructing the wavefront and saving optical hardware. The method can be implemented in real-time optical communications in atmospheric turbulence environments.